Women's Representation in Pond's Age Miracle Advertisement “Perawatan Esktra untuk Kamu yang Luar Biasa” version on Youtube - Fani Sania Rahmawati; Fitrinanda An Nur; Iva Fikrani Deslia (Politeknik Negeri Media Kreatif, 2023)
This research aims to esxplanation about women representation in Youtube channel. This research is a qualitative research, using qualitative analysis methods. Data collection techniques in this study using observations in the form of observations made at every place contained in advertisements, documentation, and literature studies, where the results of data collection will then be processed by researchers to obtain accurate and appropriate results. Age Miracle The version of